Bilingual Conversation. - Auer, Peter (Pragmatics & beyond ;, 1984)
Code-switching and related phenomena have met with linguists' increasing interest over the last decade. However, much of the research has been restricted to the structural (grammatical) properties of the use of two languages in conversation; scholars who have tried to capture the interactive meaning of switching have often failed to go beyond more or less anecdotal descriptions of individual, particularly striking, cases. The book bridges this gap by providing a coherent, comprehensive and generative model for language alternation, drawing on recent trends and methods in conversational analysi.